Observations of ionospheric disturbances via U-shaped traces on ionograms - O. A. Laryunin (Геодинамика и тектонофизика, 2019)
The ionospheric vertical sounding is a basic technique for studying the Earth’s ionosphere. Taking into account the fact that conditions for propagation of radio waves depend on the operating frequency, diagnostics of the ionosphere is performed using digital ionosondes that measure the delays of decameter radio signals of different frequencies. An ionogram is a display of the data produced by an ionosonde. It is a graph of the virtual reflection height of the ionosphere (actually, time between transmission and reception of a radio signal) versus sounding frequency.Vertical and near-vertical ionograms provide the major share of information about the space-temporal structure of the ionospheric plasma above the ionosonde. Of particular interest is investigating dynamic processes from the series of ionograms taken once each minute. Studying seismic ionospheric effects by minute ionograms can be highly informative. It is known that the parameters of the ionospheric layers can significantly vary both before and after an earthquake, and such deviations are detectable from ionosonde data. Recent observations show that the effects from an earthquake can occur at large distances from the epicenter.For instance, soundings in the Irkutsk region detected the anomalies that occurred several dozens of minutes after the main shock of the 11.03.2011 earthquake in Japan. At the initial phase, the anomaly was recordedas a multicusp structure in the ionogram, which was probably related tothe multiple layers of the ionosphere. This structure was interpreted by iterative reconstruction of the electron density profile in a one-dimensional approximation (stratified ionosphere), and the interperation was published. At the next phase, the ionograms showed a U-shaped structure with a specificmultiple reflection. Multipath propagation is usually associated with additional off-vertical ray paths, which are caused by traveling ionospheric disturbances (TIDs). In this regard, it is appropriate to use a 2D model of electron density, depending on both the vertical and horizontal coordinates.In our study, geometric optics approximation was used to simulatevertical ionograms under the conditions of strong horizontal gradients of electron density. The study results show that different positions of the U-shaped structure with respect to the main trace of the ionogram can be obtained for a single TID. Specific ray paths forming the additional traces of the ionogram are described.Depending on the TID location, the U-shaped structure can occur with or without a specificmultipath reflection.